A Framework for Analyzing Broadly Engaged Philosophy of Science - Kathryn S. Plaisance; Kevin C. Elliott (Philosophy of Science, 2021)
Philosophers of science are increasingly interested in engaging with scientific communities, policymakers, and members of the public; however, the nature of this engagement has not been systematically examined. Instead of delineating a specific kind of engaged philosophy of science, as previous accounts have done, this paper draws on literature from outside the discipline to develop a framework for analyzing different forms of broadly engaged philosophy of science according to two key dimensions: social interaction and epistemic integration. Clarifying the many forms of engagement available to philosophers of science can advance future scholarship on engagement and promote more strategic engagement efforts.